1983
DOI: 10.1177/096032718300200212
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Poisoning from the Ingestion of a Permanent Wave Solution of Mercuric Chloride

Abstract: 1 A woman developed severe mercury intoxication from ingestion of about 2.5 g of mercuric chloride. 2 Antidotal treatment with a dithiol (BAL i.m.) and a monothiol (tiopronin i.v.) was started promptly. 3 Dialysis treatment thereafter markedly increased the elimination of mercury, thus hastening recovery. 4 It is suggested that chelating agents associated with dialysis are an effective treatment for mercury poisoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Marzulli and Brown (1972) found that the use of skin lightening creams containing inorganic mercury salts result in substantial absorption and accumulation in the body. Repeated application of these skin toning creams could cause cumulative effects of prolonged low level mercury exposure, which could lead to a nephritic syndrome (Giunta et al, 1983;Rosenman et al, 1986;Enwonwu, 1987). Mercury can also be transferred from the mother to the fetus during pregnancy (Kuhnert et al, 1981;Lauwerys et al, 1987).…”
Section: Fig 1 Apparatus For Mercury Determination By Cold Vapour Atmentioning
confidence: 99%
“…Marzulli and Brown (1972) found that the use of skin lightening creams containing inorganic mercury salts result in substantial absorption and accumulation in the body. Repeated application of these skin toning creams could cause cumulative effects of prolonged low level mercury exposure, which could lead to a nephritic syndrome (Giunta et al, 1983;Rosenman et al, 1986;Enwonwu, 1987). Mercury can also be transferred from the mother to the fetus during pregnancy (Kuhnert et al, 1981;Lauwerys et al, 1987).…”
Section: Fig 1 Apparatus For Mercury Determination By Cold Vapour Atmentioning
confidence: 99%
“…Marzulli and Brown (1 972) found that the use of skin-lightening creams containing inorganic mercury salts cause substantial absorption and accumulation in the body. Repeated applications of these skin-lightening creams could cause cumulative effects of prolonged low-level mercury exposure, which could lead to a nephrotic syndrome as shown in previous studies (Giunta et al, 1983;Rosenman et al, 1986;Enwonwu, 1987). Women, especially during pregnancy and lactation, could also be at risk since a previous study by Lauwerys et al (1 987) reported a case of a woman who had recently given birth and who had used a soap during pregnancy and lactation containing 1% mercury as mercuric iodide and a mercury-containing cream.…”
Section: Discussionmentioning
confidence: 69%
“…Several studies have shown that it is possible to induce permanent kidney dysfunction by exposure to nephrotoxic chemicals during prenatal periods (Kavlock & Gray, 1983a, 1983Neubert et al, 1 985;Lauwerys et al, 1987). A recent study by Boadi et al (1 992) has shown that exposure of placental cells to mercury causes accumulation of the metal in the placental membrane and lowers the membrane fluidity, which may affect membrane function and cause damage to the developing fetus.…”
Section: Al-saleh a N D I Al-doushmentioning
confidence: 99%
“…Hemodialysis may have some ability to remove mercury in association with dimercaprol and there is some limited evidence of benefit in this context [29,30]. Most other evidence suggests a low efficacy of extracorporeal elimination methods including hemodialysis in combination with chelators [18,31].…”
Section: Discussionmentioning
confidence: 99%